2013
DOI: 10.1071/cp13006
|View full text |Cite
|
Sign up to set email alerts
|

Soil potassium—crop response calibration relationships and criteria for field crops grown in Australia

Abstract: The Better Fertiliser Decision for Crops (BFDC) National Database holds historic data for 356 potassium (K) fertiliser rate experiments (431 treatment series) for different rain-fed grain crops and soil types across Australia. Bicarbonate-extractable K (Colwell soil-test K) is the most extensively used soil test reported in the database. Data are available for several crop species grown on a range of soil types from all states except Tasmania. Species represented and number of treatment series in the database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…The critical value (90% relative dry matter) for the NH 4 OAc K method was 91 mg kg −1 at low root density (large pots) in all soils. While there are few reported studies developing critical soil test K values using the NH 4 OAc K method in the literature, Brennan and Bell reported a critical Colwell K critical value of 40–64 mg kg −1 for grain yield of wheat in field condition, with the range related to contrasting soil types 55 . This value was much lower than the 114 mg K kg −1 value we derived in this study, with the difference attributed to differences in plant growth stage, root density, water content and access to greater soil volumes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The critical value (90% relative dry matter) for the NH 4 OAc K method was 91 mg kg −1 at low root density (large pots) in all soils. While there are few reported studies developing critical soil test K values using the NH 4 OAc K method in the literature, Brennan and Bell reported a critical Colwell K critical value of 40–64 mg kg −1 for grain yield of wheat in field condition, with the range related to contrasting soil types 55 . This value was much lower than the 114 mg K kg −1 value we derived in this study, with the difference attributed to differences in plant growth stage, root density, water content and access to greater soil volumes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The benchmark of 20 kg grain/mm plant-available water suggested by French and Schultz (1984) was reached only in 2014. We cautiously rule out other potential nutritional constraints, with S and K concentrations above levels considered to limit yield (Anderson et al 2013;Brennan and Bell 2013), although K appeared marginal in the lower layers of the topsoil (Table 1). Research elsewhere has shown that applications of K to waterlogged wheat can significantly increase yield (Belford et al 1992).…”
Section: Effect Of Management On Crop N-fertiliser Recovery and Produmentioning
confidence: 99%
“…Therefore, distribution of soil K forms is influenced by many agroenvironmental factors, such as soil parent materials (Askegaard et al, 2004;McLean and Watson, 1985;Öborn et al, 2005), degree of soil weathering (Andrist-Rangel et al, 2006;Barré et al, 2008;Johnston and Goulding, 1990), topography (Kozar et al, 2002;Winzeler et al, 2008) and nutrient balance (Bertsch and Thomas, 1985;Simonsson Geoderma 290 (2017) , 2007). Despite the natural abundance of K in soils (Askegaard et al, 2004;Schroeder, 1978), certain regions of the world, such as Australia, China and Iran, present crop K deficiencies over large areas due to particular pedoclimatic conditions or long-term underfertilization of K (Brennan and Bell, 2013;Hseung, 1980;Ji-yun, 1997;Malakouti, 1999;Römheld and Kirkby, 2010). In Europe, soil K deficiencies are not widespread (Tóth et al, 2013), but deficiencies or reduction of soil K are reported at the regional scale, especially in countries around the Baltic Sea and in the United Kingdom (Andrist-Rangel et al, 2010;Tóth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%